2021
DOI: 10.1088/1361-6668/abc56a
|View full text |Cite
|
Sign up to set email alerts
|

Metallographic analysis of 11 T dipole coils for High Luminosity-Large Hadron Collider (HL-LHC)

Abstract: For next-generation accelerator magnets for fields beyond those achievable using Nb-Ti, Nb 3 Sn is the most viable superconductor. The high luminosity upgrade for the Large Hadron Collider (HL-LHC) marks an important milestone as it will be the first project where Nb 3 Sn magnets will be installed in an accelerator. Nb 3 Sn is a brittle intermetallic, so magnet coils are typically wound from composite strands containing ductile precursors before heat treating the wire components to form Nb 3 Sn. However, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In order to evaluate the adverse effects of mechanical and brittle fracture behavior, researchers report a large number of experimental results. Including direct or indirect evaluation of the mechanical properties of Nb 3 Sn filaments, Nb 3 Sn wires, Rutherford cables and coils [30][31][32][33][34], as well as their critical performance experiments under coupling fields. West and Rawlings [35] observed that the polycrystalline Nb 3 Sn filament failed in an intergranular fracture manner without any previous dislocations by scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the adverse effects of mechanical and brittle fracture behavior, researchers report a large number of experimental results. Including direct or indirect evaluation of the mechanical properties of Nb 3 Sn filaments, Nb 3 Sn wires, Rutherford cables and coils [30][31][32][33][34], as well as their critical performance experiments under coupling fields. West and Rawlings [35] observed that the polycrystalline Nb 3 Sn filament failed in an intergranular fracture manner without any previous dislocations by scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In the longitudinal cross-section, few cracks were observed in the strands located at the edge of the cable-called kink, see figure 1. They are mainly oriented in the longitudinal direction of the sub-element, named longitudinal cracks in figure 17(c) and in [1,2], or straight cracks in [21]. Other cracks oriented with wave shape around the porosity in the core of the sub-elements are also visible, named wavy cracks in figure 17(c) and in [21].…”
Section: Metallographic Analysismentioning
confidence: 99%
“…To study the electromechanical degradation of Nb 3 Sn cable-in-conduct-conductors (CICC) used in fusion reactors, metallographic observations were performed after electromechanical loadings in [9][10][11][12][13][14]. For accelerator magnets, Balachandran et al [21] performed post-mortem metallographic analysis of an 11 T dipole short model coil and of Nb 3 Sn stack samples, composed of ten cables, subjected to transverse pressure. Cracks were observed in the dipole coil resulting in degraded magnet performance.…”
Section: Introductionmentioning
confidence: 99%
“…(3) becomes a limit form of Eqs. (2). The stress and strain in the equation depend on macro-variables and satisfy the general equilibrium equation.…”
Section: Brief Review Of the Homogenization Theorymentioning
confidence: 99%
“…In addition, in a quench analysis of the magnet, it was found that the degradation of some coils was due to the fracture of filaments in the strand caused by excessive prestress [2]. Therefore, it is necessary to evaluate the stress of coils with internal microstructures.…”
Section: Introductionmentioning
confidence: 99%